Development of S-PWM voltage source inverter for induction motor drives - Siti Nursyuhada, Mahsahirun (2017)
Cage induction motor (Cage-IM) is one of the main prime mover in many industrial sectors. It provides wide range of torque production, robust and lower life cycle cost relatively to other types of motor. However, with the constructional simplicity, cage-IM tradeoff control complexity. This is due to the coupling of field and armature where the rotor magnetization is depends on the stator part. The simplest way to drive cage-IM is by implementation of series resistor at the stator terminal. But this technique is not suitable for high power IM as the heat dissipated at the resistor will make the operation of IM less power efficient. The implementation of cycloconverter circuit offers other alternative but the circuit is quite complex and less efficient as the device will used power switches at active region instead of switch mode. On the other hand, Voltage Source Inverter (VSI) implementing S-PWM to provide adjustable power to the IM. S-PWM waveforms control the switching of the power switches bridge to create DC to AC conversion. In this research, the 3-phase McMurray bridge topology is implemented. This 2 levels 3 legs topology is among the most commonly used in real application. An open loop IM drive implementing S-PWM VSI is simulated using SIMULINK. The results are comparatively analyzed through comparison with SV-PWM VSI to verify the system simulation model. Voltage and current at the stator terminal are measured and analyzed at transient and steady state to study the harmonics distortion as well as IM performance. The results shows that S-PWM VSI is capable to drive IM with 80.23% and 16.86% total harmonics distortion for voltage and current respectively. At transient state 265% electromagnetic torque overshoot occurs and the system took 0.2s for setting time. This performance results are consistent for NEMA Class B IM. The S-PWM circuit is designed with the aid of SPICE software. A 3-phase sinusoidal waves, a Centre-aligned triangle wave, 3-phase S-PWM comparator modules are implemented with operational amplifier circuit configurations of specific ICs. The designed circuits are applied for real hardware implementation and the results are compared with the simulated results. DC offset, ringing noises, amplitude and frequency errors occur on the real hardware model which are not presented by the simulation results. These errors are managed by manual adjustment of the reference modulating wave (Vref), carrier signal (Vcarrier) though Rv adjustment knob and the amount of supplied voltage of the ICs (VCC, VEE). The isolation between control circuit module (S-PWM generator) and the high voltage side of the bridge is implemented using opto coupler ICs. For IM drives integration, IR2130 bridge driver is used to provide deadtime to S-PWM wave pairs as well as interface the control circuit with the IGBTs module and IM. The developed S-PWM inverter module is capable to drive 0.4 hp cage-IM at rated speed with better power utilization as compared to the conventional variable resistance implementation.